The Malawi integrated in-service teacher education programme: an experiment with mixed-mode training - Kunje, Demis (International Journal of Educational Development, 2002)
Malawi adopted free primary education in 1994 following the democratic election of a new government. This resulted in a massive increase in the demand for primary teachers. Pre-career, full-time teacher education was replaced by the Malawi integrated in-service teacher education programme (MIITEP). This was a mixed-mode system where periods of college-based training alternated with distance and local level support for training with a school base. The programme was introduced in 1997 and has successfully trained over 18,000 teachers. This paper describes the programme, and presents evidence on different elements of its implementation. It draws attention to its strengths and weaknesses and some of the conditions which need to be met to improve its quality.
KerkoCite.ItemAlsoKnownAs: 10.1016/S0738-0593(01)00065-7 4752638:NWJ2G9C9
Keywords: In-service; Malawi; Primary teacher education; School-based training; _C:Malawi MWI